2002
DOI: 10.1021/jp0205719
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nonpolar Solvation Dynamics in Supercritical Lennard−Jones Fluids in Terms of the Solvent Dynamic Structure Factor

Abstract: The nonpolar solvation dynamics in Lennard−Jones fluids is discussed in terms of the relationship with the dynamic structure factor of neat solvent, using the theoretical expression that describes the solvation correlation function as the superposition of solvent dynamic structure factors at various wavenumbers. Several expressions for the coupling strength between the state transition of the solute and the solvent density modes are examined with respect to their abilities to predict the static fluctuation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Several effective medium approximations have been proposed in the literature to deal with the problem of the local density profile. 10 They replace the solute-solvent interaction potential in the orientational component of the chemical potential of solvation (v 0s θ(r) in Eq. ( 13)) with an effective solute-solvent coupling including the information about the solute-solvent density correlations (direct solute-solvent correlation function in the surrogate 6,10,77 and density functional 9 theories or vertex in the modecoupling formulation 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several effective medium approximations have been proposed in the literature to deal with the problem of the local density profile. 10 They replace the solute-solvent interaction potential in the orientational component of the chemical potential of solvation (v 0s θ(r) in Eq. ( 13)) with an effective solute-solvent coupling including the information about the solute-solvent density correlations (direct solute-solvent correlation function in the surrogate 6,10,77 and density functional 9 theories or vertex in the modecoupling formulation 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 They replace the solute-solvent interaction potential in the orientational component of the chemical potential of solvation (v 0s θ(r) in Eq. ( 13)) with an effective solute-solvent coupling including the information about the solute-solvent density correlations (direct solute-solvent correlation function in the surrogate 6,10,77 and density functional 9 theories or vertex in the modecoupling formulation 11 ). However, all such approximations are heavily dependent on the detailed knowledge of the solute-solvent distribution function which is available only for solutes of simple shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local solvation structure and especially the local density augmentation (LDA) effects of several, mainly dilute, supercritical solutions have been investigated by employing experimental techniques, statistical mechanical theories and molecular simulations. These studies have revealed important information about the solvation in SCFs.…”
Section: Introductionmentioning
confidence: 99%
“…Using these techniques several authors have provided important information about the local density inhomogeneities (LDI) in pure SCF, , as well as in SC solutions. Furthermore, in our previous studies we have focused on the static and dynamic behavior of aforementioned LDIs and residence dynamics in pure SCFs, , and the effect of intermolecular interactions upon them …”
Section: Introductionmentioning
confidence: 99%